2023
DOI: 10.3390/jof9080789
|View full text |Cite
|
Sign up to set email alerts
|

Meyerozyma caribbica Isolated from Vinasse-Irrigated Sugarcane Plantation Soil: A Promising Yeast for Ethanol and Xylitol Production in Biorefineries

Abstract: The production of fuels and other industrial products from renewable sources has intensified the search for new substrates or for the expansion of the use of substrates already in use, as well as the search for microorganisms with different metabolic capacities. In the present work, we isolated and tested a yeast from the soil of sugarcane irrigated with vinasse, that is, with high mineral content and acidic pH. The strain of Meyerozyma caribbica URM 8365 was able to ferment glucose, but the use of xylose occu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…High viscosity might have influenced yeast metabolic activity and fermentation kinetics [ 49 ]. A study focused majorly on ethanol production and partially on xylitol on M. caribbica URM 8365 with biomass hydrolysate also reported that at condition of 1.6 gL −1 acetic acid in the medium, only xylose metabolism was hindered while the uptake of glucose and total ethanol production remained unaffected [ 6 ]. RSHM1 was chosen for further research after considering all the factors influencing the feasibility of the fermentation process, such as incubation time, nutrient consumption, and total inhibitor accumulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High viscosity might have influenced yeast metabolic activity and fermentation kinetics [ 49 ]. A study focused majorly on ethanol production and partially on xylitol on M. caribbica URM 8365 with biomass hydrolysate also reported that at condition of 1.6 gL −1 acetic acid in the medium, only xylose metabolism was hindered while the uptake of glucose and total ethanol production remained unaffected [ 6 ]. RSHM1 was chosen for further research after considering all the factors influencing the feasibility of the fermentation process, such as incubation time, nutrient consumption, and total inhibitor accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…The biotransformation of xylose into xylitol from hemicellulose of lignocellulosic biomass such as rice straw is also of interest to modern biorefineries, as it can be processed into a variety of bio-based chemical products after the cellulosic fraction has been used for ethanol production. According to the US Department of Energy, xylitol is one of the top twelve carbohydrate-derived chemicals with the potential to be a co-product of plant biomass-led bio-refinery [ 4 ] for instance, with lactic acid [ 5 ] and ethanol [ 6 ] which is one of the most advanced productions from lignocellulosic biomass. Xylitol has been approved for use in food products in over 50 countries for dietary purposes, particularly for food, pharmaceutical and odontological applications.…”
Section: Introductionmentioning
confidence: 99%
“…The biotransformation of xylose into xylitol from hemicellulose of lignocellulosic biomass such as rice straw is also of interest to modern biorefineries, as it can be processed into a variety of bio-based chemical products after the cellulosic fraction has been used for ethanol production. According to the US Department of Energy, xylitol is one of the top twelve carbohydrate-derived chemicals with the potential to be a co-product of plant biomassled bio-refinery [4] for instance, with lactic acid [5] and ethanol [6] which is one of the most advanced productions from lignocellulosic biomass. Xylitol has been approved for use in food products in over 50 countries for dietary purposes, particularly for food, pharmaceutical and odontological applications.…”
Section: Introductionmentioning
confidence: 99%
“…The achievement of effective xylitol bioconversion through fermentation is contingent upon many parameters, including temperature, pH, aeration conditions, substrate concentration, and the existence of other molecules apart from xylose, such as glucose. In addition, the xylose solution undergoes a conversion process, resulting in the formation of the xylitol solution [9]. The adequate preparation of the medium is crucial for achieving good fermentation of xylitol.…”
Section: Introductionmentioning
confidence: 99%